Threat-related amygdala activity is associated with peripheral CRP concentrations in men but not women. (April 2017) - Swartz, Johnna R.; Prather, Aric A.; Hariri, Ahmad R.
Highlights: Association between peripheral C-Reactive Protein and amygdala activity is tested. In men, but not women, higher CRP is associated with higher amygdala activity. Amygdala activity is a potential pathway linking inflammation to internalizing risk. Abstract: Increased levels of peripheral inflammatory markers, including C-Reactive Protein (CRP), are associated with increased risk for depression, anxiety, and suicidality. The brain mechanisms that may underlie the association between peripheral inflammation and internalizing problems remain to be determined. The present study examines associations between peripheral CRP concentrations and threat-related amygdala activity, a neural biomarker of depression and anxiety risk, in a sample of 172 young adult undergraduate students. Participants underwent functional MRI scanning while performing an emotional face matching task to obtain a measure of threat-related amygdala activity to angry and fearful faces; CRP concentrations were assayed from dried blood spots. Results indicated a significant interaction between CRP and sex: in men, but not women, higher CRP was associated with higher threat-related amygdala activity. These results add to the literature finding associations between systemic levels of inflammation and brain function and suggest that threat-related amygdala activity may serve as a potential pathway through which heightened chronic inflammation may increase risk for mood and anxiety problems.